Multifunctional Hydrogels for Advanced Cancer Treatment: Diagnostic Imaging and Therapeutic Modalities - Kyung Kwan Lee; Kwangmo Go; Eonjin Lee; Hongki Kim; Seonwook Kim; Ji-Hyun Kim; Min Suk Chae; Jin-Oh Jeong (Gels, 2025)
Multifunctional hydrogels represent an emerging technological advancement in cancer therapeutics, integrating diagnostic imaging capabilities with therapeutic modalities into comprehensive, multifunctional systems. These hydrogels exhibit exceptional biocompatibility, biodegradability, high water retention capacity, and tunable mechanical properties, enabling precise drug delivery while minimizing systemic side effects. Recent innovations in stimuli-responsive components facilitate intelligent, controlled drug release mechanisms triggered by various stimuli, including changes in pH, temperature, magnetic fields, and near-infrared irradiation. Incorporating diagnostic imaging agents, such as magnetic nanoparticles, fluorescent dyes, and radiolabeled isotopes, substantially improves tumor visualization and real-time therapeutic monitoring. Multifunctional hydrogels effectively integrate chemotherapy, photothermal therapy, photodynamic therapy, immunotherapy, and their synergistic combinations, demonstrating superior therapeutic outcomes compared to conventional methods. Particularly, injectable and in situ-forming hydrogels provide sustained local drug delivery postoperatively, effectively reducing tumor recurrence. However, challenges persist, including initial burst release, mechanical instability, regulatory barriers, and scalability concerns. Current research emphasizes advanced nanocomposite formulations, biofunctionalization strategies, and innovative manufacturing technologies like 3D bioprinting to facilitate clinical translation. This review comprehensively summarizes recent advancements, clinical applications, and future perspectives of multifunctional hydrogel systems for enhanced cancer treatment, underscoring their potential to revolutionize personalized oncology.